"Princesas em greve": as possibilidades da literatura infantil para educar crianças feministas - Rodrigues, Beatriz Caroline Aparecida (Universidade Federal de São Carlos, 2023)
“Which children's literature works to use in the classroom to ensure a feminist education for children?” This work is built around this question. From it, there arises the need to search for and analyze children's literature works that can offer this possibility. For this purpose, it was necessary to start the journey with a bibliographic research to be able to conceptualize the use of children's literature for children's education and how the feminist identity is formed. It was also necessary to search for children's literature works that somehow addressed themes of the feminist movement, such as: prevention of sexual abuse, empowerment, deconstruction of beauty standards, etc., and analyze, through the Content Analysis method, the works showing their potentialities. Throughout the research, it was concluded that children's literature is an excellent tool for critical formation of children and youth, and the mapping showed that we have excellent works available, the analyzed works proved to be competent and full of possibilities.
"Princesses on strike": the possibilities of children's literature to educate feminist children
Keywords: Literatura infantil; Children's Literature; Feminist education; Critical education; Gender; Educação feminista; Educação crítica; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO